Determination of Mosaicity in Oriented Stacks of Lipid Bilayers - Nagle, John F. (Soft Matter, 2015)
Two methods of measuring the misorientation of domains in oriented multilamellar stacks of lipid bilayers superficially appeared to give different values for the mosaic spread. It is first shown that the traditional rocking method and a newer ring method give the same value of the mosaic spread when the two types of data are similarly analyzed. Both indicate a long-tailed, nearly Lorentzian, mosaic distribution function. Our primary innovation is the analysis of ring data as a function of the rocking angle. For our best oriented DOPC sample, this analysis is consistent with a single Lorentzian mosaic distribution function with width 0.05°. In contrast, samples of DMPC indicate a more complex mosaic distribution and larger widths.